Intra- and inter-rater reliability in the assessment and classification of the longitudinal plantar arch of children 6 to 10 years of age - Thiago Weyk de Oliveira Beliche; Tânia Cristina Dias da Silva Hamu; Rafaela Noleto dos Santos; Roberta Carneiro de Toledo; Thailyne Bizinotto; Celmo Celeno Porto; Cibelle Kayenne Martins Roberto Formiga (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aims: This study aimed to analyze the intra- and inter-rater reliability in the assessment and classification of the longitudinal plantar arch of children from 6 to 10 years old in the eyes-open (EO) testing condition. Methods: A total of two-hundred and seventy-eight Brazilian children (556 feet), boys and girls, from 6 to 10 years of age participated in the study. The children's feet were examined on a baropodometric platform, and the Staheli index was used for calculating the plantar arch index. Footprint analyses were performed at two different times, with an interval of 7 to 10 days, by three physical therapists in a single testing condition, resulting in 3,336 footprints. To determine the reliability of the continuous measurements, the Intraclass Correlation Coefficients (ICC) with 95% confidence intervals (CIs), Standard error of the mean (SEM), absolute value and percentage, and the Minimum Detectable Change (MDC) were calculated. To determine the reliability of the longitudinal arch classification, inter-rater reliability was evaluated by Weighted Fleiss Kappa Coefficient and the test-retest reliability was estimated by Weighted Cohen Kappa Coefficient. Results: Regarding inter-rater reliability, we observed values of ICC ranging from 0.79 to 0.96; thus, the results were classified as substantial to excellent reliability), being the lowest ICC values occur for line B, mainly in the first assessments. SEM ranges from 0.08 to 0.21 (percentage: 3.74 to 28.7), being the best, the lowest SEM values occur for Plantar Arch Index assessments and the MDC varies between 0.22 and 0.59. Regarding intra-rater reliability, the results indicated excellent reliability: values of ICC range from 0.92 to 0.99, being the lowest ICC values also occurs for line B analysis. SEM ranges from 0.03 to 0.20 (percentage: 2.32 to 26.6), being the lowest SEM values occur for Plantar Arch Index assessments and MDC varies between 0.09 and 0.54. Analyzing the inter-rater reliability for the longitudinal arch classifications, we observed values of Weighted Fleiss Kappa Coefficient ranging from 0.83 to 0.87, expressing almost perfect agreement among the raters before and after evaluations. The test-retest reliability of the longitudinal arch classification resulted in values of Weighted Cohen Kappa Coefficient ranging from 0.80 to 0.996, expressing substantial to almost perfect agreement intra-rater. Conclusion: The study showed high reliability in the clinical assessment of the longitudinal plantar arch index of children from 6 to 10 years of age indicating that the Staheli method is applicable to pressure platform assessments with intra- and inter-rate reliability.